Pengembangan Mutu Guru di MAN 3 Jember Tahun 2013: Teacher Quality Development at MAN 3 Jember in 2013 - Abdul Munif (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2013)
The development of human resources, especially teachers in Islamic educational institutions, is a necessity to survive in the era of globalization. Teachers are a crucial component and the key to the success of the learning process in schools. The quality of a school is often associated with the quality of students and teachers, who interact directly with students in the classroom. Teacher quality development is directed toward creating professional educators with high work ethics and a strong commitment to values imbued with the spirit of worship. However, the current reality still highlights concerns about the low quality of Islamic education teachers due to unclear development directions. Therefore, a proper, reliable, and comprehensive teacher resource development strategy is needed to achieve the desired goals. Pengembangan mutu sumber daya manusia, khususnya guru di lembaga pendidikan Islam, merupakan suatu keharusan untuk tetap bertahan di era globalisasi. Guru adalah komponen penting dan kunci keberhasilan proses pembelajaran di sekolah. Mutu sebuah sekolah sering dikaitkan dengan mutu siswa dan guru, yang berinteraksi langsung dengan siswa di kelas. Pengembangan mutu guru diarahkan pada pembentukan pendidik yang profesional, beretos kerja tinggi, dan berkomitmen pada nilai-nilai ibadah. Namun, realitas saat ini masih banyak mengeluhkan rendahnya mutu guru pendidikan Islam karena arah pengembangannya belum jelas. Oleh karena itu, diperlukan strategi pengembangan sumber daya guru yang tepat, andal, dan komprehensif untuk mencapai tujuan yang diinginkan.